Pengaruh Pendekatan Metaphorical Thinking Terhadap Pemahaman Konsep Matematika Distance - Rafita, Ani Adella; Suryanti, Sri (Postulat : Jurnal Inovasi Pendidikan Matematika, 2020)
Mathematics should be studied systematically and regularly and it must be presented with a clear structure, therefore an appropriate learning approach is needed. One approach to learning in mathematics is metaphorical thinking. This approach can encourage students to think metaphors to understand a mathematical concept. This study aims to determine the effect of the metaphorical thinking approach on understanding mathematical concepts. This type of research is experimental. Research subjects class VIII-E and VIII-F in MTs Negeri 2 Lamongan. The research instrument used to measure understanding of mathematical concepts in the material Surface Area of Flat Side Space is in the form of description. The results showed that students’ understanding of mathematical concepts using the metaphorical thinking approach (experimental class) was better than students who used the deductive learning approach (control class). Data analysis used two independent samples t-test which showed a sig value of 0.011 <α = 0.05, then reject Ho. Thus the learning of mathematics in the material Surface Area Build Flat Side Space by using the metaphorical thinking approach affects the understanding of students’ mathematical concepts